Інноваційний розвиток техніки для молочного скотарства - Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна; Boltianska, Natalia; Маніта, Ігор Юрійович; Манита, Игорь Юрьевич; Manita, Ihor (ТДАТУ, 2020)
UK: В статті проаналізована технологія виробництва молока, що застосовується на молочно-товарних фермах України. Надано рекомендації застосування технологій для дійного стада. Наведено відмінні елементи цих технологій при використанні підстилки, на килимках або на матах і при різних поєднаннях систем утримання та принципів обслуговування. Виявлені наступні тенденції розвитку технологій і технічних засобів. 1. Підвищення ефективності виробництва молока за рахунок розширення масштабів освоєння безприв'язного способу утримання корів з доїнням в доїльних залах і доїльними роботами, а також з максимальним використанням генетичного потенціалу тварин та енергії корму. 2. Нормована годівля тварин, для чого доцільно використовувати для роздавання кормів змішувачі-роздавачі, кормові станції, або стаціонарні кормоприготувальні пункти в поєднанні з мобільними роздавачами. 3. Створення та застосування енергозберігаючих екологічно безпечних технологій та автоматизованих комплексів машин для прибирання гною 4. Створення і застосування роботів для очищення стійл, кормових і гнойових проходів. RU: В статье проанализирована технология производства молока, что применяется на молочно-товарных фермах Украины. Даны рекомендации применения технологий для дойного стада. Приведены отличительные элементы этих технологий при использовании подстилки, на ковриках или матах и при различных сочетаниях систем содержания и принципов обслуживания. Выявлены следующие тенденции развития технологий и технических средств. 1. Повышение эффективности производства молока за счет расширения масштабов освоения беспривязного способа содержания коров с доением в доильных залах и доильными роботами, а также с максимальным использованием генетического потенциала животных и энергии корма. 2. Нормированная кормление животных, для чего целесообразно использовать для раздачи кормов смесители-раздатчики, кормовые станции, или стационарные кормоприготовительные пункты в сочетании с мобильными раздатчиками. 3. Создание и применение энергосберегающих, экологически безопасных технологий и автоматизированных комплексов машин для уборки навоза. 4. Создание и применение роботов для очистки стойл, кормовых и навозных проходов. EN: Technical re-equipment of livestock through the use of highly efficient sets of machines is an important and necessary factor in the reproduction and development of livestock in the future. Under the influence of new technology is the improvement of the organizational and technological bases of production, the technology of preparation of feed for feeding: grinding, blending, cleaning and balancing rations, provision of animal habitat in accordance with their physiological needs, which leads to improvement and enhancement of the utilization of genetic potential of animals, increase of economic indicators of production, quality of production improves and the cost of implementation, reduced losses, and inefficient use of raw materials. The article analyzes the technology of milk production that is applied to dairy farms of Ukraine. This recommendation of applying the technology to dairy cattle in Ukraine based on loose-box contents cows. Given the distinctive elements of these technologies in the use of litter on rugs or mats and with different combinations of systems of content and service principles. The analysis of domestic and foreign experience and the conducted research revealed the following trends in the development of technologies and technical means. 1. Improving the efficiency of milk production due to the expansion of the scale of the development of theloose ways of keeping cows with milking in milking parlours and milking robots, as well as with maximum use of genetic potential of animals and energy of the feed. 2. Normalized feeding animals, which is useful for feeding mixer feeder, feeding station, orfixed feed preparation items in conjunction with the mobile distributors. 3. The creation and use of energy-saving, environmentally friendly technologies and automated complexes of machines for cleaning manure from livestock buildings, transport it to the place of storage and processing. 4. Creating and using robots to clean stalls, feed and manure passages, which can replace humans in operations
Инновационное развитие техники для молочного скотоводства
Innovative development of technology for dairy cattle
Keywords: молочно-товарна ферма; виробництва молока; техніка; інноваційний розвиток; производство молока; инновационное развитие; dairy farm; milk production; technology; innovative development